The Reliability and Feasibility of the HESPER Web to Assess Perceived Needs in a Population Affected by a Humanitarian Emergency a Humanitarian Emergency - Karin Hugelius (International Journal of Environmental Research and Public Health, 2021)
Needs assessment is essential in the humanitarian response, and perceived needs can be associated with the levels of health in populations affected by humanitarian emergencies. This study aimed to evaluate the reliability and feasibility of The Humanitarian Emergency Settings Perceived Needs Web (HESPER Web) in a humanitarian context and to compare perceived needs of a random walk study sample with a self-selected study sample recruited though social media. The study context was the Dadaab refugee camp in Kenya. An alternate forms reliability evaluation and a feasibility evaluation was conducted. In total, 308 refugees participated in the study. HESPER Web was found to be reliable and usable for assessing needs, with an intraclass correlation coefficient (ICC) of 0.88, Cohen’s κ between 0.43 and 1.0 and a first priority need rating match of 81%. The HESPER Web was positively experienced, and the self-recruited study sample reported similar levels of needs and similar demographics as the randomized sample. The participants reported several unmet needs. HESPER Web offers a reliable tool for needs assessment in humanitarian emergencies where web-based surveys are considered as practical and suitable. It offers new possibilities for conducting remote assessments and research studies that include humanitarian populations that are rarely included in such evaluations.